Philosophy Of Law And The Development Of Law As A Normative Legal Science - Dwi Indriati, Ervina; ana, Sary; Nugroho, Nunung (CV. Inara, 2022)
Philosophy is an attempt to fundamentally study and express a man's depiction in the world towards the afterlife. The object is material and formal. Through this normalization of human behavior, the law traces almost all areas of human life. Legal philosophy analyzes the legal principles and answers questions related to legal problems in both normative and empirical juridical forms so that legal objectives can be achieved, namely for improvement in human life. The method of approach used is normative juridical, analytical descriptive research specifications are expected to provide a detailed, systematic, and comprehensive picture based on the correlation of data with each other on the Philosophy of Law and The Development of Law Normative Legal Sciences. The type and source of data used are secondary as a primary data source, consisting of primary legal materials, secondary legal materials, and tertiary legal materials. The data analysis method is qualitative. The legal theory does speak of many things that can fit into the political field of law, legal philosophy, legal science, or a combination of those three fields. Therefore, the theory of law may at some point talk about something universally numbered. Still, he may be talking about very specific things according to a particular place. The function of the law is not enough just as social control, but more than that. The function of the law expected today is to move the community to behave by new ways of acting or behaving by the provisions of the law.